Consumption, Health, and Disposability in SpongeBob SquarePants. (27th May 2015) - Piatti-Farnell, Lorna; Leahy, Deana; Gray, Emily; Cutter-Mackenzie, Amy; Eames, Chris
Abstract In recent years, food scholarship has extended its preoccupation with consumption to interrogating the relationship between eating, culture and waste, and their effects on the environment. Simultaneously, food-related concerns have also become a recurrent part of popular culture, where examples from children's television provide fertile ground for discussion. This article analyses the multiple representations of food, consumption, and waste in Stephen Hillenburg's animated series SpongeBob SquarePants. Focusing on the specific food-related pedagogical philosophies that seem recurrent in the series, and following in Henry Giroux's footsteps by seeing a link between popular culture and educational structures, my discussion unravels the show's engagement with the over-consumption of fast food, the acculturation of the burger as the American meal par excellence, and environmental issues of 'over-production'. I aim to show how, ultimately, SpongeBob SquarePants offers an evaluation of the connection between consumption, health, and disposability in contemporary Western societies.